2014
DOI: 10.1016/j.cbpc.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure investigating the estrogenic potency of estriol in Japanese medaka (Oryzias latipes)

Abstract: The growth, development, and ERα and Vtg-I gene expressions of Japanese ricefish (Oryzias latipes; medaka) exposed to different concentrations of estriol (E3), including one environmentally relevant concentration, during embryo-adult life stages were evaluated. At the early life stage, fertilized eggs were exposed to 5, 50, 500, 5000 ng/L E3 for 15 days, and the hatched fry were exposed continuously to the same concentrations for an additional 15 days. Exposure to 500 and 5000 ng/L E3 resulted in adverse effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
(86 reference statements)
0
6
1
Order By: Relevance
“…Similarly to the present results, a continuous exposure of freshly fertilized eggs of medaka (Oryzias latipes) to 200 g/L bisphenol A (BPA; ca 18 ng/L EEQ) led to early hatch (Ramakrishnan and Wayne, 2008). Contrary, a continuous estriol (E3) exposure to 500 and 5000 ng/L (ca 0.2 and 1.7 g/L EEQ) delayed time to hatch and reduced hatchability of medaka (Lei et al, 2014). In salmonids, offspring of phytosterol-exposed maturing lake trout (Salmo trutta lacustris) hatched earlier through parental transfer (Lehtinen et al, 1999).…”
Section: Hatchcontrasting
confidence: 74%
“…Similarly to the present results, a continuous exposure of freshly fertilized eggs of medaka (Oryzias latipes) to 200 g/L bisphenol A (BPA; ca 18 ng/L EEQ) led to early hatch (Ramakrishnan and Wayne, 2008). Contrary, a continuous estriol (E3) exposure to 500 and 5000 ng/L (ca 0.2 and 1.7 g/L EEQ) delayed time to hatch and reduced hatchability of medaka (Lei et al, 2014). In salmonids, offspring of phytosterol-exposed maturing lake trout (Salmo trutta lacustris) hatched earlier through parental transfer (Lehtinen et al, 1999).…”
Section: Hatchcontrasting
confidence: 74%
“…There are growing accounts of the deleterious effects of estrogen contaminant exposure on fish populations. , Previous studies of estrogen (e.g., E2β, 17α-ethynylestradiol (EE2), estriol) and wastewater treatment plant effluent exposure during specific temporal or developmental stages ,,,, or through complete life cycles ,, have established that exposure can lead to impaired reproductive success. However, from regulatory or management perspectives, it is difficult to prioritize decisions or mitigation efforts without a clear understanding of the most critical stages of susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hirai et al document differential disruption of fecundity and fertility in Japanese medaka ( Oryzias latipes ) following E2β exposure at two periods, fertilization to 31 days post fertilization and fertilization to 81 days post fertilization . While numerous studies have documented impaired fertility and fecundity in fish following chronic exposures to estrogens and estrogen mimics within both the organizational and activational phases, ,,,, there remains a paucity of information regarding differential reproductive effects of exposure within defined developmental stages. This study examined reproductive dysfunction following exposure during four critical stages of development (susceptibility) in medaka: gonad development, gonad differentiation, development of SSC, and gonad maturation.…”
Section: Introductionmentioning
confidence: 99%
“…This is important for determining the lowest effective dose on organisms as the doses in acute toxicity studies are much higher. On the example of estriol, the selected (chronic toxicity) study observed effects for 90 days with an effective dose of 46.5 ng/L (Lei et al, 2014), while another (acute toxicity) study performed with the same substance that only lasted one day, used a dose higher than 100 mg/L (Li, 2013).…”
Section: Ecotoxicological Datamentioning
confidence: 99%